2018
DOI: 10.1038/s41467-018-07202-0
|View full text |Cite
|
Sign up to set email alerts
|

A conserved enhancer regulates Il9 expression in multiple lineages

Abstract: Cytokine genes are regulated by multiple regulatory elements that confer tissue-specific and activation-dependent expression. The cis-regulatory elements of the gene encoding IL-9, a cytokine that promotes allergy, autoimmune inflammation and tumor immunity, have not been defined. Here we identify an enhancer (CNS-25) upstream of the Il9 gene that binds most transcription factors (TFs) that promote Il9 gene expression. Deletion of the enhancer in the mouse germline alters transcription factor binding to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 68 publications
4
45
0
Order By: Relevance
“…Commitment to the TH9 lineage is the result of a number of TFs acting in concert. Recent ChIP‐sequencing studies identified binding of IRF4, BATF, STAT5, STAT6, PU.1, GATA3, and FOXO1 at five different regulatory regions of IL9 including the promoter (Koh et al, ). IL4, required in vitro in addition to TGFβ, promotes TH9 differentiation, in part by pSTAT6 inhibiting TGFβ‐induced FOXP3 and T‐bet expression and therefore inhibiting Treg and TH1 polarization (Dardalhon et al, ; Kaplan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Commitment to the TH9 lineage is the result of a number of TFs acting in concert. Recent ChIP‐sequencing studies identified binding of IRF4, BATF, STAT5, STAT6, PU.1, GATA3, and FOXO1 at five different regulatory regions of IL9 including the promoter (Koh et al, ). IL4, required in vitro in addition to TGFβ, promotes TH9 differentiation, in part by pSTAT6 inhibiting TGFβ‐induced FOXP3 and T‐bet expression and therefore inhibiting Treg and TH1 polarization (Dardalhon et al, ; Kaplan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…BATF and IRF‐4 cooperatively contribute to Th9 cell development . CNS‐25 acts as an enhancer upstream of the il9 gene binding most IL‐9 promoting transcription factors, as could be shown in mice . TL1A, which represents a member of the TNF superfamily, promotes Th9 differentiation, and function through induction of transcriptional BATF3 expression in mice and humans .…”
Section: Il‐9 Producing Th2‐like Cellsmentioning
confidence: 93%
“…(Bi et al, 2017;Buttrick et al, 2018;Campos Carrascosa et al, 2017;Kaplan et al, 2015). Like other cytokine genes, the Il9 locus has a complex enhancer structure (Koh et al, 2018;Schwartz et al, 2019).…”
Section: Regulation Of Expression Of G C Family Cytokinesmentioning
confidence: 99%